Girls like us - Alger, Cristina (G.P. Putnam's Sons, 2019)
"From the celebrated and bestselling author of The Banker's Wife, worlds collide when an FBI agent investigates a string of grisly murders on Long Island that raises the impossible question: What happens when the primary suspect is your father?"--